Orientalist representation of the Muslim opening campaign - Bajuri@Mok, Nur Aainaa; Zakariya, Hafiz (IIUM Press, 2017)
This study examines Orientalist portrayals and representations of the Futuhat Islamiyyat. It utlizes historical methodology in analyzing this important topic.